The Role of Central Kalimantan Indonesian Ulama Council (MUI) in Encouraging Muslim Participation in Regional Elections: Perspective of Fatwa on Prohibition of Abstention - Ahmidi, Ahmidi; A.S. Pelu, Ibnu Elmi; Noor Ihsan, Reza (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study examines and proposes several roles that Central Kalimantan Indonesian Ulama Council [Henceforth (MUI)] can play in encouraging Muslim participation in regional elections [Henceforth (Pilkada or Pemilukada)] through the perspective of fatwa on prohibition of abstention [Henceforth (golput)]. As a religious institution, MUI holds a strategic role in guiding Muslims on political issues, particularly regarding Pemilukada. In a democratic system, participation is crucial for electing leaders who can ensure people’s welfare and fulfill their responsibilities. The fatwa on the prohibition of golput, issued by MUI, serves as a normative foundation for Muslims to exercise their voting rights in Pilkada. This study utilized normative juridical by reviewing various secondary sources and literature relevant to the topic. The findings reveal that Central Kalimantan MUI can promote political awareness among Muslims in the region, with MUI actively participating in public outreach and campaigns about the importance of political participation. Furthermore, collaboration with local institutions such as the Indonesian Da’wah Institution, religious counselors, and media platforms is key in promoting Muslim voter participation through the fatwa on the prohibition of golput. This study also found that the fatwa has been highly effective in raising awareness among Muslims about the significance of their political involvement in regional elections.